Compulsory English Online Learning Practices - Muhammad Iqbal Ripo Putra (IKIP PGRI Pontianak, 2020)
This study aimed to investigate online learning practices in several schools studied in Pontianak City. This research was conducted in 4 schools in Pontianak. The results of this study are expected to describe the implementation of online learning practices in Pontianak City, the challenges they face in designing online learning, and looking for potentials that can be used as solutions for improving online learning in the future. The method used was a descriptive qualitative approach, where the interview guide is used as an instrument for data collection methods. In this study was implemented in each school uses an online learning process, namely asynchronous and synchronous. By using applications such as Whatsapp, Google Forms, Google Classroom, Telegram, and GoodEdu as asynchronous and using Google meet and zoom as synchronous. Thematic analysis and cross-case analysis were used to analyze the data. The interview consisted of 15 question items consisting of 3 aspects. The challenges they face were the lack of readiness to use technology, lack of phone credit and cell phone facilities, difficulty understanding the material, lack of motivation and enthusiasm for learning, and difficulties in assessing students. And the potential for future improvements is to provide socialization and guidance on IT, support facilities for the online learning process, improve skills and strategies in teaching, teachers provide unlimited remedial and good cooperation between schools, teachers, parents, and students.